American Short Story - Cocchiarale, Michael, 1966-; Emmert, Scott, 1962- (Ipswich, Massachusetts : Salem Press, a division of EBSCO Information Services, Inc. ; Amenia, NY : Grey House Publishing, 2015)
This collection of critical essays on the American short story examines the historical and literary contexts for the development of the genre and includes readings of specific authors and works--
Critical contexts. The short story cycle in American fiction / Jennifer J. Smith ; The mystery of existence: the American short story in criticism and theory / Nicholas Birns ; Postcolonial literature post-Proulx : how a border-crossing short story writer reconditions the category / Hannah Jocelyn ; The metafiction of Tim O'Brien and Richard Russo / Stacy Esch -- Critical readings. Knowledge and power in Henry James' "In the Cage" / Linda Simon ; "The Blue Hotel" and Stephen Crane's American violence / Marc Dziak ; "A Study in Pain" : musical variations and Ernest Hemingway's "The Gambler, the Nun, and the Radio" / Nicole J. Camastra ; Famine in the cabin : reading the hungry in Richard Wright's Uncle Tom's Children / McKinley E. Melton ; "The Country in the Woman" : "voice" in a "new" story by Zora Neale Hurston and the revival of formalist criticism / Robert C. Evans ; The "vanishing American" : remembering Weldon Kees' short fiction / Ola Madhour ; Girls in search of a viable identity in Eudora Welty's The golden apples / Imola Bulgozdi ; Identity and globalization in Jhumpa Lahiri's "Unaccustomed Earth" / Rossitsa Terzieva-Artemis ; Sherman Alexie's defiant brand of humor in Blasphemy / Tara E. Friedman ; Reading short short stories, seriously / Randall Brown.
Edition statement supplied by publisher.
Includes bibliographical references (pages 233-236) and index.
Keywords: Short stories, American -- History and criticism